Explaining the visible and the invisible: Public knowledge of genetics, ancestry, physical appearance and race in Colombia. (December 2015) - Schwartz-Marín, Ernesto; Wade, Peter
Using data from focus groups conducted in Colombia, we explore how educated lay audiences faced with scenarios about ancestry and genetics draw on widespread and dominant notions of nation, race and belonging in Colombia to ascribe ancestry to collectivities and to themselves as individuals. People from a life sciences background tend to deploy idioms of race and genetics more readily than people from a humanities and race-critical background. When they considered individuals, people tempered or domesticated the more mechanistic explanations about racialized physical appearance, ancestry and genetics that were apparent at the collective level. Ideas of the latency and manifestation of invisible traits were an aspect of this domestication. People ceded ultimate authority to genetic science, but deployed it to work alongside what they already knew. Notions of genetic essentialism co-exist with the strategic use of genetic ancestry in ways that both fix and unfix race. Our data indicate the importance of attending to the different epistemological stances through which people define authoritative knowledge and to the importance of distinguishing the scale of resolution at which the question of diversity is being posed.